Clinical Assessment of a Lateral Epicondylar Anatomical Plate for the Stabilization of Humeral Condylar Fractures in Dogs - Jones, Rebecca L.; Tomlinson, Andrew W.; Barnes, Duncan M.; Hood, Rebecca S.; McClement, Jamie P.; Ogden, Daniel M.; Owen, Mark A.; Onyett, Jeremy R.; Walton, Myles B. (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective To report the use of a Lateral Epicondylar Anatomical Plate for the management of humeral condylar fractures (HCF) in dogs.Study Design Medical records of dogs with HCF stabilized using the Lateral Epicondylar Anatomical Plate at six UK veterinary referral centres between April 2018 and February 2021 were reviewed. Long-term follow-up (>6 months) was obtained via owner questionnaire, which incorporated the Liverpool Osteoarthritis in Dogs clinical metrology instrument.Results Sixty-two HCF were treated in 61 dogs (44 lateral condylar fractures [LCF] and 18 intracondylar (T/Y) fractures [ICF]). Fifty-one dogs were Spaniels or Spaniel crossbreeds. Intraoperative contouring of the plate was required for one dog—a French Bulldog. Postoperative complications occurred in 14/42 LCF and 6/18 ICF; overall there were 14 minor, 8 major, and 2 catastrophic complications. On final follow-up imaging, there was evidence of partial or complete osseous continuity of the condylar part of the fracture 32/53 HCF (24/39 LCF and 8/14 ICF) and lateral epicondylar part of the fracture in 53/53 HCF (39/39 LCF and 14/14 ICF). At final reexamination, 20/28 dogs with LCF and 5/13 dogs with ICF were not lame and the remaining dogs demonstrated mild lameness. According to the owner questionnaire, 17/17 dogs with LCF and 8/10 dogs with ICF returned to full limb use and median Liverpool Osteoarthritis in Dogs scores were 2/52 for LCF and 6.5/52 for ICF.Conclusion The Lateral Epicondylar Anatomical Plate can be used successfully for the surgical stabilization of HCF in dogs.
Keywords: elbow; fracture fixation; fracture repair systems; humeral condylar fracture; anatomical orthopaedic implants